Deviation of The Use of Discipline and Punishment in The novel Animal Farm by George Orwell - Citra, Nabila; Pratiwi, Dyani Prades (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2025)
Discipline and punishment makes people obey the rules and have been used from the ancient times to the presents. Animal Farm is one of the novels that present these issues. This study aims to show the discipline and punishment contained in this novel and how these methods become the tools of producing power relation. The method of this study is qualitative method, while the analysis will be analysed with using Foucault’s theory about discipline and punishment. The result of the study shows that The system of implementing the discipline and punishment produce the power relation between the ruler and the animals in the farm. There is a lot of abuse in this novel due to several factors such as greed and selfishness, and also there is a lack of education for the animals which results in the animals being unable to do anything. Due to the wrong system that is not implemented accordingly and the deviation of the use of discipline and punishment, many unexpected events also occur. Starting with the animals committing a rebellion that was originally intended for peace and freedom together, but after the rebellion, the opposite occurred, which is the colonization between fellow animals.